A Rota do Rosário como estratégia de reforço do contínuo institucional católico no Norte Pioneiro e Campos Gerais do Paraná (2008-2023) - Souza, Helison Lázaro de (2024)
The present study seeks to analyze the establishment of the Rota do Rosário (2008-2023) as a religious and tourist route in the 21st century, in the context of supply and demand. This initiative, promoted by the Diocese of Jacarezinho (PR), is part of the continuous efforts of the Roman Catholic Church (ICAR) related to religious tourism, encompassing the northeastern region (Norte Pioneiro) and parts of the central-eastern region (Campos Gerais) of Paraná. Proposed as an “instrument of evangelization”, the Rota do Rosário extends beyond its religious purpose, with expanded promotional efforts creating itineraries that cater to the growing demand for diverse experiences and positioning itself within the context of consumption in contemporary society. The study aims to understand the Rota do Rosário within historical, geographical, and religious contexts, analyzing it as a continuation of diocesan actions adapted for the 21st century and representing part of the institutional integration updates initiated at the beginning of the 20th century. In this way, various offerings such as pilgrimages, religious processions, and religious tourism are explored, highlighting the intersections between Ecotourism, Rural Tourism, Adventure Tourism, Leisure Tourism, Business Tourism, and Cultural Tourism. The partnership and support of political and business organizations are emphasized, which, together with the religious organization, promote culture, history, economy, tourism, and, above all, the Catholic faith. The Rota do Rosário, by articulating itself as a project of territorial Catholic revival, offers diverse practices. The sanctuaries constitute the main points of interest in promoting the Route, considered the central nucleus of diocesan action, gathering tourist elements around them. The Rota do Rosário is clearly designed to appeal to both religious and non-religious people, with discourses directed at the latter as “a path back to God”. Walking, cycling, horseback riding, or using other means of transportation allows for varied experiences along the religious and tourist route, which presents multiple meanings, whether related to identity or aimed at entertainment and leisure.